Предмет: Математика,
автор: mariuashmariua
Реши уравнение. Ответ: x = X 3 3 4 .. 4 2 - 3 1
Приложения:
Ответы
Автор ответа:
0
Ответ:
6.
Пошаговое объяснение:
(х/3 + 1/4) / 6 3/4 + 2/3 = 1
(х/3 + 1/4) / 6 3/4 = 1 - 2/3
(х/3 + 1/4) / 6 3/4 = 1/3
х/3 + 1/4 = 6 3/4 • 1/3
х/3 + 1/4 = (27•1)/(4•3)
х/3 + 1/4 = (9•1)/(4•1)
х/3 + 1/4 = 9/4
12•х/3 + 12•1/4 = 12•9/4
4х + 3 = 27
4х = 27 - 3
4х = 24
х = 24 : 4
х = 6
Ответ: 6.
Проверка:
(6 : 3 + 1/4) / 6 3/4 + 2/3 = 1
(2 + 1/4) : 6 3/4 + 2/3 = 1
2 1/4 : 6 3/4 + 2/3 = 1
9/4 • 4/27 + 2/3 = 1
1/3 + 2/3 = 1
1 = 1- верно.
Похожие вопросы
Предмет: Алгебра,
автор: arturkrukov809
Предмет: Английский язык,
автор: o3575475
Предмет: Алгебра,
автор: ussasaamong
Предмет: Биология,
автор: pvkusnyasha5